Reference intervals for plasma cystatin C and plasma creatinine in adults using methods traceable to international calibrators and reference methods. Issue 6 (24th March 2018) - Erlandsen, Erland Jørn; Randers, Else
Abstract : Introduction: The aim of this study was to establish reference intervals for plasma cystatin C and creatinine in adults using the Gentians cystatin C method traceable to the international calibrator standard ERM‐DA471/IFCC and a creatinine method traceable to the IDMS (Isotope Dilution Mass Spectrometry) creatinine reference method. Methods: Blood samples were collected from 304 healthy blood donors (152 men and 152 women between 17 and 66 years old) with 30‐31 men and 30‐31 women in each ten‐year interval. Plasma cystatin C was analyzed using the Gentian Cystatin C assay on a Roche cobas c702 analyzer, and plasma creatinine was analyzed using the CREA Plus assay on the Roche Modular P analyzer. Results: The nonparametric reference intervals for plasma cystatin C were 0.58‐1.00 mg/L in women (median 0.78 mg/L, range 0.56‐1.06 mg/L) and 0.62‐1.04 mg/L in men (median 0.79 mg/L, range 0.61‐1.07 mg/L). The Mann‐Whitney U test revealed no gender‐related difference in plasma cystatin C ( P  = .21). A common reference interval in women and men was calculated to be 0.61‐1.01 mg/L (median 0.79 mg/L, range 0.56‐1.07 mg/L). The nonparametric reference interval for plasma creatinine was 52‐89 μmol/L in women (median 69 μmol/L, range 52‐92 μmol/L) and 61‐108 μmol/L in men (median 86 μmol/L, range 56‐118 μmol/L). The Mann‐Whitney U test revealed a gender‐related difference in plasma creatinine ( P  < .0001). Conclusion: In conclusion, we have established reference intervals for plasma cystatin C and creatinine in adults using methods traceable to international standards.